PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA BENGKEL JAYA ABADI MOTOR KARANGGAWANG - Anik Safitri; Febryantahanuji (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
The Karanggawang, Demak location, service quality, and facilities offered by Jaya Abadi Motor Workshop are all examined in this study in connection to customer satisfaction. The study used quantitative methods to choose hundreds of volunteers. SPSS version 26 was utilized for the analysis, which employed multiple linear regression. Service quality, location, and resources all affect customer satisfaction, the results showed. An Adjusted R2 score of 0.440 indicates that these three factors explain 44% of the variation in customer satisfaction.